The Effect of Project-Based Learning (PBL) Method on Improving Students' Writing Ability - Petrus Jacob Pattiasina; Hidayatul Hikmah; Purwo Adi Nugroho (PT. Anagata Sembagi Education, 2024)
Education plays a crucial role in shaping intelligent, moral and responsible individuals. The project-based learning (PBL) model emerges as an innovative approach that focuses not only on knowledge transfer, but also the development of students' critical skills, creativity and collaboration. This study aims to analyze the effect of PBL on students' writing ability compared to conventional learning methods. Through a literature study, the data sources obtained show that PBL increases students' engagement, confidence, and in-depth understanding of the material. Students are actively involved in project planning and implementation, which allows them to apply knowledge in a real context, resulting in a more meaningful learning experience. The findings confirm the importance of PBL as an effective method in improving students' writing skills, as well as providing recommendations for educators to integrate PBL in the educational curriculum to create a generation that is ready to face global challenges.